2014
DOI: 10.1007/s11764-014-0390-2
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up patterns of cancer survivors: a survey of Canadian radiation oncologists

Abstract: Survivors may be increasingly followed by family physicians. Better coordination between oncologists and family physicians, including the use of survivorship care plans, may facilitate this transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Toutefois, de nombreuses études réalisées au Canada et ailleurs dans le monde ont montré que le médecin de première ligne demeure le coordonnateur principal des soins pendant la période de survie et qu'il peut prodiguer efficacement les soins dans les cas de cancer à faible risque (Del Guidice et al, 2009;Mao et al, 2009;Grunfeld et al, 1995Grunfeld et al, , 1996Grunfeld et al, , 1999Grunfeld et al, , 2006Sisler, Brown et Stewart, 2004;Wattchow et al, 2006;Wood, 1993). Ye, Cheung, Goddard, Horvat et Olson (2015) ont établi que, règle générale, les radio-oncologues se chargent du suivi des patients aux cancers plus complexes (ceux qui touchent le système nerveux central, le tractus gastro-intestinal, la tête et le cou, et l'appareil gynécologique et génito-urinaire) à cause de la toxicité liée au traitement et de la possible nécessité de traitements supplémentaires. De l'avis des oncologues, les médecins de première ligne auraient besoin d'une formation plus poussée, ainsi que de lignes directrices plus détaillées, pour assurer le suivi ici.…”
Section: Discussionunclassified
“…Toutefois, de nombreuses études réalisées au Canada et ailleurs dans le monde ont montré que le médecin de première ligne demeure le coordonnateur principal des soins pendant la période de survie et qu'il peut prodiguer efficacement les soins dans les cas de cancer à faible risque (Del Guidice et al, 2009;Mao et al, 2009;Grunfeld et al, 1995Grunfeld et al, , 1996Grunfeld et al, , 1999Grunfeld et al, , 2006Sisler, Brown et Stewart, 2004;Wattchow et al, 2006;Wood, 1993). Ye, Cheung, Goddard, Horvat et Olson (2015) ont établi que, règle générale, les radio-oncologues se chargent du suivi des patients aux cancers plus complexes (ceux qui touchent le système nerveux central, le tractus gastro-intestinal, la tête et le cou, et l'appareil gynécologique et génito-urinaire) à cause de la toxicité liée au traitement et de la possible nécessité de traitements supplémentaires. De l'avis des oncologues, les médecins de première ligne auraient besoin d'une formation plus poussée, ainsi que de lignes directrices plus détaillées, pour assurer le suivi ici.…”
Section: Discussionunclassified
“…Most of these studies have relied on small patient-populations[47] or physician surveys. [48-51] One study reporting the use of surveillance imaging in a large, nationally representative population found that 86.8% of patients received some kind of imaging study from 4 to 8 months after surgical resection of early stage NSCLC (47.6% CT and 68.5% CXR). [26] Although these findings highlight the use of imaging early in the surveillance period, adherence to guidelines over the entire 2 year surveillance period recommended by NCCN and ACCP was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have relied on small patient-populations [47] or physician surveys. [48][49][50][51] One study reporting the use of surveillance imaging in a large, nationally representative population found that 86.8% of patients received some kind of imaging study from 4 to 8 months after surgical resection of early stage NSCLC (47.6% CT and 68.5% CXR). [26] Although these findings highlight the use of imaging early in the surveillance period, adherence to guidelines over the entire 2 year surveillance period recommended by NCCN and ACCP was not measured.…”
Section: Discussionmentioning
confidence: 99%